Independence of the prognostic value of tumor suppressor protein expression in ovarian adenocarcinomas: A multivariate analysis of expression of p53, retinoblastoma, and related proteins. Issue 5 (1st August 2003) - Tachibana, M.; Watanabe, J.; Matsushima, Y.; Nishida, K.; Kobayashi, Y.; Fujimura, M.; Shiromizu, K.
Abstract : Accurate estimation of prognosis of ovarian cancer is difficult. For this report, in a group of 73 patients with ovarian adenocarcinomas, clinical factors and protein expression status of p53, retinoblastoma (Rb), and related proteins were evaluated for potential prognostic values. Clinical factors included FIGO stage, age, histopathologic type, and protein expression of p53, Rb, MDM2, p14 ARF, p21 WAF(1)/CIP(1) was determined by an immunohistochemical technique. Univariate Cox proportional hazard regression analysis was used to determine the significant prognostic value of FIGO stage ( P < 0.0001), p53 status (0.0021), and patient age ( P = 0.0255), and we report here, for the first time, the significant ( P = 0.0072) prognostic value of Rb status. Histopathologic type and MDM2, p14 ARF, p21 WAF(1)/CIP(1) status did not show any prognostic value. To examine further the independence of prognostic values, we next applied multivariate analysis: We found that FIGO stage ( P < 0.0001) and p53 status ( P = 0.0108) were independent prognostic factors, while age and Rb status were not. Independence of prognostic value of p53 has heretofore been controversial, but we found a definite independent prognostic value for p53 status in ovarian adenocarcinomas. We also found that selection of appropriate antibodies for immunohistochemistry was essential to obtain significant results. We used five kinds of antibodies for p53 immunolocalization, and correlation with prognosis was obtained by three of these with different grades of statistical significance.